TINJAUAN HUKUM BIDANG PEMBINAAN DAN PENGAMANAN TERHADAP ANGGOTA KEPOLISIAN NEGARA REPUBLIK INDONESIA YANG MELAKUKAN PENYALAHGUNAAN NARKOBA - Aulia Rahman Tohari (Universitas 17 Agustus 1945 Samarinda, 2020)
ABSTRACTIn Indonesia, the Nakoba problem is a national problem that threatens the achievement of state goals and can damage the nation's young generation, therefore the government mandates the granting of authority to enforce the law against drug abuse to the National Narcotics Agency and the Indonesian National Police. But in reality there are some police officers who even abuse their authority by participating in the use and distribution of illegal drugs or drugs. This can cause a loss of public confidence in the police. Based on this description, the main problems in this paper are: (1) How Criminal Responsibility Before Entering General Crimes Against Police Members Conducting Narcotics Abuse Crimes and (2) How the Process of Sentencing against Police Members Performs Drug Abuse. the approach to the problem used is normative juridical. The data used are primary and secondary data, data collection and data processing with literature. In dealing with granting criminal sanctions against police officers who abuse drugs, Law Number 35 of 2009 concerning Narcotics. In this provision not only applies to members of the police, but also to other communities that have been proven to have abused narcotics. In Article 12 paragraph (1) Government Regulation Number 2 of 2003 concerning Discipline Regulations of Members of the Police of the Republic of Indonesia confirms that